Poverty mapping based on first order dominance with an example from Mozambique - Channing Arndt; M. Azhar Hussain; Vincenzo Salvucci; Finn Tarp; Lars Peter Østerdal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We explore a novel first order dominance (FOD) approach to poverty mapping and compare its properties to small area estimation. The FOD approach uses census data directly; is straightforward to implement; is multidimensional allowing for a broad conception of welfare; and accounts rigorously for welfare distributions in both levels and trends. An application to Mozambique highlights the value of the approach, including its advantages in the monitoring and evaluation of public expenditures. We conclude that the FOD approach to poverty mapping constitutes a useful addition to the toolkit of policy analysts.
Keywords: C15; C81; I32; 330; first order dominance; poverty mapping; small area estimation; multidimensional poverty measurement; public expenditure evaluation; Mozambique